Orthodontically induced external apical root resorption with clear aligners compared to fixed appliance treatment: An umbrella review - Madhanraj Selvaraj; Bhaskar Nivethitha; Balasubramanian Madhan (Journal of Oral Biology and Craniofacial Research, 2025)
Introduction: Orthodontically induced external apical root resorption (OIEARR) is an inevitable complication of orthodontic treatment. This study aimed to provide the existing highest level of evidence on OIEARR in patients undergoing orthodontic treatment with clear aligners compared to fixed orthodontics. Materials and methods: A comprehensive electronic database search was conducted using predefined search terms without any restrictions on language and year of publication. Systematic reviews with or without meta-analysis comparing the OIEARR in fixed and clear aligner groups were only considered. The overlap of primary studies was assessed using the GROOVE tool, and two reviewers graded the quality assessment of included reviews independently using AMSTAR 2. A random effects meta-analysis was carried out for homogenous CBCT data. Results: Out of 1181 articles, eight reviews were eligible; only four considered meta-analyses. A high overlap of 31 primary studies was reported, with 22 included in meta-analyses overlap. AMSTAR 2 tool outlined that the quality of the reviews was critically low in four, with two each being high and low quality. Meta-analysis between the aligner and fixed appliance groups revealed a significant mean difference of 0.62 mm in maxillary central incisors and 0.65 mm in maxillary lateral incisors. The heterogeneity of included primary studies ranged from moderate to high. Conclusion: The incidence and severity of OIEARR are lower in clear aligners than in fixed appliance groups. The results need to be cautiously inferred due to the low to moderate quality of the evidence. Therefore, there is a future need for high-quality RCTs, considering the associated risk factors.